Point and fault rupture stochastic methods for generating simulated accelerograms considering soil effects for structural analysis - Estêvão, João M. C. (2014)
Many seismic codes such as the Eurocode 8 allow the use of simulated accelerograms for structural analysis, provided that the samples used are adequately qualified with regard to the seismogenetic features of the sources and to the soil conditions appropriate to the site. In the present work we studied the possibility of using stochastic methods for that purpose. In that context, two computer programs for stochastic ground motion simulation considering soil effects were developed: ACELGER based on a point source model, and SIMULSIS based on a finite fault model. Both programs were used to simulate the 1992 Landers earthquake for their validation. Simulation results obtained with these programs were compared between each other to better understand the influence of source fault plane geometry in structural response. Results seem to indicate that finite fault models are better options for structural analysis, because only with them it is possible to reproduce directivity effects and non stationary structural response observed with recorded accelerograms. SIMULSIS was also used to carry out the simulation of the 1980 Azores earthquake (January 1, 1980, Portugal) in two islands, with different local site conditions, which were compared with observed damages, to better understand the influence of soil geology in structural response, and showed that site effects have a major importance in structural behaviour.